Digestible Lysine Requirements of Male Turkeys in Their First Six Weeks - Firman, Jeffre (International Journal of Poultry Science, 2004)
Two floor pen trials were conducted using 1200 and 960 Nicholas White toms, respectively, in order to determine the digestible lysine requirements during the first 6 week growth (7 to 18 and the 23 to 37 days) period. Poults were fed a typical corn, soybean meal (SBM) and pork meal based diet until the start of each trial, when they were weighed and sorted into 48 floor pens in a curtain-sided building. Dietary treatments included eight levels of digestible lysine ranging from 1.10 to 1.45% in the first experiment and 1.02 to 1.37% in the second experiment. In each experiment, a positive control was added at the expense of three replicates of the highest lysine level. The lysine deficient basal diet was corn, SBM and pork meal with a crude protein level of 21.7% for the first period and 20.75% for the second period. The positive control was also corn, SBM and pork meal and was formulated on a total AA basis to meet nutrient requirements set by the NRC. All diets were iso-caloric (3100kcal/kg). Lysine-HCL (98.5%) was used for the titrations and glutamic acid was titrated inversely to keep nitrogen levels similar. The experiments were set up as randomized complete blocks. Birds fed digestible lysine levels of 1.30% and above in the first experiment and 1.19% and above in the second experiment had weight gains that were equal to the positive control (P<. 05). No feed:gain differences were observed between treatments in either experiment. Splined regression analysis determined the requirement for optimum bodyweight gain to be 1.31% digestible lysine for the 7 to 18 day period and 1.19% for the 23 to 37 day period.